Religious vocabulary in the Great Dictionary of the Polish Language PAN - Przybylska, Renata (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The article describes the religious vocabulary and the way it is presented in the Great Dictionary of the Polish Language of the Polish Academy of Sciences. The author characterizes the main conceptual circles in which the religious vocabulary is focused, and analyzes the chronological, stylistic and pragmatic qualifiers used in the description. She draws attention to new lexical units, not listed in previous dictionaries.